Warcross - Lu, Marie, 1984- (2017)
"When teenage coder Emika Chen hacks her way into the opening tournament of the Warcross Championships, she glitches herself into the game as well as a sinister plot with major consequences for the entire Warcross empire"--
Keywords: Internet games -- Juvenile fiction; Computer crimes -- Juvenile fiction; Hackers -- Juvenile fiction; Spy stories; Bounty hunters -- Juvenile fiction; Young adult fiction; Science fiction; Science fiction; Spy fiction; Fiction; Juvenile works; Science fiction; Spy stories; Young adult works